Tetramethyl rhodamine methyl ester (TMRM) is suitable for cytofluorometric measurements of mitochondrial membrane potential in cells treated with digitonin - Floryk, D; Houstĕk, J (Bioscience reports, 1999)
A new method for cytofluorometric analysis of mitochondrial membrane potential deltapsi has been developed by using TMRM as a cationic, mitochondrial selective probe. The method is based on limited treatment of cultured cells with digitonin which permeabilises the plasma membrane and leaves mitochondria intact. The resulting signal of TMRM-stained cells thus represents only the probe accumulated in mitochondria. Fibroblasts and cybrids were used as a model cell systems and optimal conditions for digitonin treatment and staining by TMRM were described. The TMRM signal collapsed by valinomycin, KCN and antimycin A and FCCP titration was used to gradually lower deltapsi and characterise the stability of deltapsi. The method is suitable for sensitive measurement of deltapsi in different types of cultured cells.
Keywords: Indicators and Reagents; fluorescenční barviva; intracelulární membrány; membránové potenciály; indikátory a reagencie; Membrane Potentials; Mitochondria; Fluorescent Dyes; Fluorometry; Rhodamines; lidé; Intracellular Membranes; fluorometrie; Digitonin; digitonin; mitochondrie; Humans; rhodaminy